PENGARUH STRUKTUR MODAL, PERENCANAAN PAJAK, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA(BEI) PADA TAHUN 2021-2023 - Desy Natalia Sipahutar; Abubakar Arief (STMIK Widuri Jakarta, 2025)
Earnings management is a type of action undertaken by management to regulate earnings in the preparation of financial statements to align with specific objectives that may harm other stakeholders while benefiting themselves. This study aims to determine the influence of capital structure, tax planning, and firm size on earnings management. The sample was obtained from manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2021-2023. The independent variables in this study are capital structure, tax planning, and firm size, while the dependent variable is earnings management. This study employs a purposive sampling method. The data analysis model used is panel data regression analysis processed using EViews-12 software. This study is expected to provide information regarding the impact of earnings management, making it one of the considerations in decision-making. Based on the results of the study, it was found that capital structure has no effect on earnings management, tax planning has no effect on earnings management, and firm size has no effect on earnings management.